2019
DOI: 10.1002/rse2.105
|View full text |Cite
|
Sign up to set email alerts
|

Improved assessment of mangrove forests in Sundarbans East Wildlife Sanctuary using WorldView 2 and TanDEM‐X high resolution imagery

Abstract: Recent developments of remote sensing techniques which can capture both the structure and function of the ecosystem provide a more representative view of the landscape. These unique Earth observations were used to help improve traditional forestry surveys by providing species‐specific land cover classes for mangrove forests in the Sundarbans East Wildlife Sanctuary. By combining optical data from WorldView2 (WV2; 2 m pixel) and a canopy height model derived using radar data from TanDEM‐X (TDX; 12 m pixel), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 59 publications
(159 reference statements)
0
15
0
Order By: Relevance
“…In terms of the methods, prior studies use a range of classification techniques such as the iterative self-organizing data analysis (ISODATA) clustering, maximum likelihood classification (MLC), hybrid, random forest (RF), classification and regression trees (CART), support vector machine (SVM), and object oriented classification among others [16,17,34,[37][38][39][40][41]43,66]. With the advent of cloud computing platforms with free access to petabytes of geospatial data, such as Google Earth Engine (GEE), it has now become increasingly accessible and straight-forward to analyze enormous amounts of satellite imagery covering large regions [37,[67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the methods, prior studies use a range of classification techniques such as the iterative self-organizing data analysis (ISODATA) clustering, maximum likelihood classification (MLC), hybrid, random forest (RF), classification and regression trees (CART), support vector machine (SVM), and object oriented classification among others [16,17,34,[37][38][39][40][41]43,66]. With the advent of cloud computing platforms with free access to petabytes of geospatial data, such as Google Earth Engine (GEE), it has now become increasingly accessible and straight-forward to analyze enormous amounts of satellite imagery covering large regions [37,[67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…This complex ecosystem is a network of numerous tidal waterways, evolving mudflats and islands of salt-tolerant mangrove species, composed of 24 "true mangrove" species and 70 "mangrove associates" including dominant tree species such as Sundri (Heritiera fomes), Gewa (Excoecaria agallocha), Goran (Ceriops decandra), and Keora (Sonneratia apetala) (Rahman, Hossain, et al, 2015). This ecosystem also supports over 1000 documented faunal species including several endangered and threatened vertebrate species such as tiger (Panthera tigris tigris), South Asian river dolphin (Platanista gangetica), Irrawaddy dolphin (Orcaella brevirostris), masked finfoot (Heliopais personatus), Northern river terrapin (Batagur baska), and saltwater crocodile (Crocodylus porosus) (Aziz & Paul, 2015;Rahman et al, 2019). cloud cover.…”
Section: Study Areamentioning
confidence: 84%
“…We found that there were 15 remote-sensing articles published on forests during the study period. Two-third of these studies used Landsat data in their analyses, while a few used MODIS [22,23], Sentinel-2 [24], and radar products (e.g., ALOS-PALSAR, TanDEM-X) [25,26]. The availability of moderate resolution (i.e., 30 m) Landsat imageries made it a popular choice of data products among the researchers.…”
Section: Sdg 151-forestsmentioning
confidence: 99%
“…Additionally, the supervised random forest [24], hierarchical [27], hybrid [30,32] and classification approaches have been used by some. Forest health assessment, habitat degradation, species composition related studies used various approaches, in addition to supervised MLC, in their analysis including OLS Ordinary Least Square (OLS) regression [22,23], unsupervised Iterative Self-Organizing Data Analysis Technique (ISODATA) [25], and Refined Gamma Maximum-A-Posteriori (RGMAP) filtering [26]. In change detection studies, classification accuracy is very important to ensure the correct estimation of land cover change [38].…”
Section: Sdg 151-forestsmentioning
confidence: 99%